Efficient Synthesis of 2,5-Diketopiperazines by Staudinger-Mediated Cyclization - Beagle, Lucas K.; Hansen, Finn K.; Monbaliu, Jean-Christophe M.; DesRosiers, Michael P.; Phillips, Angela M.; Stevens, Christian V.; Katritzky, Alan R. (Synlett, 2012)
Solution- and solid-phase Staudinger-mediated cyclizations were assessed to efficiently prepare hetero-2,5-diketopiperazines from their protected azido dipeptide thioesters under microwave irradiation. Short reaction time, good yields and ease of purification are the main assets of this methodology.
Keywords: azides; cyclization; cyclic peptides; Staudinger; methodology